Prove that tan70°=tan20°+2tan50°
Answers
Answered by
30
I have already answered this question before, So I have copy pasted it.
Given LHS = tan 70.
tan70=(tan50+tan20)/(1-tan50tan20)
tan70(1-tan50tan20)=tan50+tan20
tan70-tan70tan50tan20=tan50+tan20
tan70-tan(90-20)tan50tan20=tan50+tan20
tan70-cot20tan50tan20=tan50+tan20
tan70-(cot20tan20)tan50=tan50+tan20
tan70-(1)tan50=tan50+tan20
tan70-tan50=tan50+tan20
tan70=tan20+2tan50
LHS = RHS
Hope this helps!
Given LHS = tan 70.
tan70=(tan50+tan20)/(1-tan50tan20)
tan70(1-tan50tan20)=tan50+tan20
tan70-tan70tan50tan20=tan50+tan20
tan70-tan(90-20)tan50tan20=tan50+tan20
tan70-cot20tan50tan20=tan50+tan20
tan70-(cot20tan20)tan50=tan50+tan20
tan70-(1)tan50=tan50+tan20
tan70-tan50=tan50+tan20
tan70=tan20+2tan50
LHS = RHS
Hope this helps!
Answered by
34
Already Answered this Question So Copy Pasted It.
________________________
To Prove :
As We Know,
Now,
Thus,
Subsitute This Result in (1)
★We Get,
Hence Proved.
____________________________
Similar questions